Atomistic simulations to study the effect of helium nanobubble on the shear deformation of nickel crystal - Sharma, Abhinav Kumar; Sharma, Saurabh S; Singh, Sandeep Kumar; Parashar, Avinash (Journal of nuclear materials, 2021)
So far, many theoretical and experimental studies have investigated the detrimental effect of helium nanobubble on the mechanical properties of nuclear structural materials. In this article, efforts have been made to study the effect of helium nanobubble on the onset of plastic deformation in a single crystal Ni. The onset of plastic deformation has been quantified as a function of the orientation of slip planes with shear force and configuration of helium nanobubbles. Two configurations were generated for helium nanobubble, one with radius fixed where the He to Ni vacancy ratio was varied. In contrast, the ratio was kept constant in another configuration, and the nanobubble radius was varied. From the simulation, it was predicted that irrespective of the orientation of Ni crystal with respect to shear forces, helium nanobubble has a detrimental effect on the mechanical properties of the single-crystal Ni. Compared to the size of helium nanobubble, the higher concentration of helium atoms in the nanobubble has a more detrimental effect on mechanical strength. The focus of nuclear scientists is to develop future generation nuclear reactors and predict the safe life cycle of existing nuclear structures, which are in use for a long time. Helium nanobubbles change the mechanical behavior of underlying nuclear material in an effective manner. The results presented in this article will help in developing a better understanding of the deformation in irradiated Ni crystal.